THE GREEN PEACH APHID, MYZUS PERSICAE (SULZER): A GLOBAL PEST AND ITS SUSTAINABLE MANAGEMENT APPROACHES - JEYASHREE J; GOPIANAND L (The Bioscan, 2024)
The green peach aphid, Myzus persicae (Sulzer), is a globally distributed pest with a remarkably broad host range, infesting over 400 plant species, including several economically important crops. It is considered as a pest due to its high reproductive potential, adaptability to diverse agroclimatic zones, and ability to transmit numerous plant viruses. This review provides a comprehensive account of the global distribution and extensive host range of M. persicae, along with insights into its bio-ecology, including life cycle dynamics, feeding behaviour, and environmental adaptability. It explores various management strategies, including cultural practices, biological interventions, and chemical control measures. Special emphasis is given on the challenges posed by insecticide resistance, which significantly hampers effective chemical control. The review highlights the importance of integrated pest management (IPM) strategies that combine multiple sustainable approaches to reduce dependence on chemical inputs and mitigate resistance development. Understanding the biology and ecological interactions of M. persicae is key to designing effective, long-term management programs suited to both conventional and organic farming systems.